A People and a nation : a history of the United States - Norton, Mary Beth (Boston, Massachusetts : Houghton Mifflin Company, 1988)
This text is a condensation of the very successful second edition of a people and a nation. It preserves all the strengths of that full-length edition - its readability, its comprehensives, and most importantly, its blend of social, political, diplomatic, and economic history.
Chapter 1. The meeting of old world and new -- Chapter 2. American society takes shape -- Chapter 3. Growth and diversity -- Chapter 4. Severing the dons of empire -- Chapter 5. A revolution, indeed -- Chapter 6. Forging a national republic -- Chapter 7. Politics and society in the early republic -- Chapter 8. The empire of liberty -- Chapter 9. A market and industrial economy.
Includes index.
Keywords: UNITED STATES -- HISTORY